Nepal in the SAARC Framework: Promoting Sovereignty and National Security - Paudel, Santosh Kumar (Kutumbha vani, 2023)
Nepal's involvement in the South Asian Association for Regional Cooperation (SAARC) significantly shapes its foreign policy decisions, affecting its sovereignty and national security. This article thoroughly explores Nepal's role in SAARC, considering its history, current importance, and future implications. Using research methods backed by real evidence, it carefully examines how ideas like sovereignty and national security play out within SAARC, focusing on Nepal's stance and actions amidst changing regional circumstances. Through a detailed review of existing studies and relevant examples, the article identifies gaps in understanding and proposes research questions to fill those gaps effectively. Furthermore, it addresses the various challenges Nepal faces within the SAARC framework, suggesting ways to enhance its involvement while safeguarding its sovereignty and national security interests. The findings highlight Nepal's active participation in SAARC initiatives, such as trade agreements and disaster management frameworks, showcasing the organization as a platform for enhancing economic integration, connectivity, and regional stability. Additionally, the article reveals Nepal's strategic use of SAARC to balance its relationships with neighboring giants India and China, mitigating challenges to its sovereignty and security. Despite significant benefits, the research underscores the persistent obstacles posed by regional power dynamics, political instability, and trade imbalances. Ultimately, this article highlights the vital significance of Nepal's participation in SAARC, stressing its potential to promote stability and prosperity across South Asia.